Society 5.0—Unlocking Entrepreneurial Competencies in Farmer Scope - Achmad, Gusti Noorlitaria; Fitriansyah, Fitriansyah; Darma, Dio Caisar; Syachrani, Syaparliddin; Kurniadin, Nia (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
This study was designed to investigate the relationship between Society 5.0 and the development of entrepreneurial competencies. The research employed a questionnaire-based interview involving 159 dragon fruit farmers in the Indonesian Capital City/Ibu Kota Nusantara (IKN). The collected questionnaire data were analyzed using moderated regression techniques. The results indicate a correlation between the proposed hypotheses and the findings, demonstrating that digital skills, understanding of information technology (IT), and relevant education significantly influence adaptive attitudes and mental readiness. Furthermore, both adaptive attitudes and mental readiness have a substantial effect on entrepreneurial competence. Digital skills, understanding of IT, and relevant education, when moderated by adaptive attitudes, can enhance entrepreneurial competence. However, mental readiness does not serve as a moderating factor. These findings contribute valuable insights to both academic discourse and practical policies aimed at enhancing farmers' entrepreneurial competencies within the framework of a sustainable Society 5.0.